PEMBUATAN BIOPLASTIK BERBAHAN DASAR PATI BIJI DURIAN (DURIO ZIBETHINUS MURR.) SEBAGAI RANCANGAN MODUL PADA MATERI BIOTEKNOLOGI KELAS XII SMA - Septiami, Mona; Zulfarina, Zulfarina; Syafii, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the manufacture of bioplastics based ondurian seed starch and produce module designs on biotechnology materials in class XIISMA. This research was conducted at the Biology Education Laboratory of FKIP andthe Chemistry Laboratory of FMIPA UNRI from April to August 2019. This researchwas carried out in 2 stages: the experimental stage: the making of bioplastics fromdurian seed starch and the module design stage: an analysis of the potential of moduledesign in class XII biotechnology material High school. This study used anexperimental method using a Completely Randomized Design (CRD) consisting of 5treatments and 3 replications. The parameter in this study is the absorption ofbioplastic water. Based on the results of Analysis of Variance (ANAVA) at 5% levelshowed the making of bioplastics based on durian seed starch with the addition ofgelatin can reduce the absorption of bioplastic water (13.49%)). While based on theanalysis of the potential of the research results can be used as a module design inbiotechnology material class XII SMA in KD 3.10.Key Words: Bioplastic, Durian seeds, Durian Seeds Starch, Modul